Curcumin-Mediated Degradation of S-Phase Kinase Protein 2 Induces Cytotoxic Effects in Human Papillomavirus-Positive and Negative Squamous Carcinoma Cells - Khan, Abdul Q.; Siveen, Kodappully S.; Prabhu, Kirti S.; Kuttikrishnan, Shilpa; Akhtar, Sabah; Shaar, Abdullah; Raza, Afsheen; Mraiche, Fatima; Dermime, Said; Uddin, Shahab (Frontiers in Oncology, 2018)
Head and neck squamous cell carcinoma (HNSCC) is one of the most common cancers worldwide. The mechanisms that regulate mitogenic and anti-apoptotic signals in HNSCC are not well known. S-phase kinase-associated protein2 (SKP2), a proto-oncoprotein, play a vital role in development and progression of human malignancies as it targets cell cycle progression through degradation of G1-checkpoint CDK inhibitors - p21 (CDKN1A) and p27 (CDKN1B). The present study was designed to investigate the effect of curcumin, a natural compound isolated from rhizomes of the plant Curcuma longa, on HNSCC cell lines with and without human papilloma virus’s growth and survival by targeting SKP2 and associated signaling proteins. Our data showed that curcumin inhibits cell viability and induces apoptosis in a dose-dependent manner in human papillomavirus-positive (HPV+ and negative (HPV-) HNSCC cell lines. Our data demonstrate that curcumin-treatment or expression of SKP2 causes down-regulation of SKP2 and upregulation of p27 and p21 proteins in both types of HNCC cells. Furthermore, treatment of HPV+ and HPV- cells with curcumin causes apoptosis by involving the mitochondrial pathway and activation of caspases. In addition, treatment of HPV+ and HPV- cell lines with curcumin down-regulated the expression of XIAP, cIAP1, and cIAP2. Finally, co-treatment HNSCC with curcumin and cisplatin potentiated inhibition of cell viability and apoptotic effects. Altogether, these data suggest a novel function for curcumin, acting as a suppressor of oncoprotein SKP2 in squamous cell carcinoma cells in both HPV+ and HPV- cells, raise the possibility that this agent may have a future therapeutic role in squamous cell carcinoma.